The X-2 ADT-X: Japan's last chance fighter jet? - Bitzinger, Richard A. (2016)
Japan will soon fly its X-2 fifth-generation fighter jet for the first time, prompting the possibility of a renaissance in the country’s aircraft sector. To successfully challenge the West’s dominance of the global fighter aircraft business, Japan must synchronise many technological, economic, and political factors, a “harmonic convergence” that is hardly assured.